Precipitation morphology of niobium and its influence on the microstructure and mechanical properties of Fe–Mn–Al–C lightweight steel - Litu Huo; Xiaoyuan Bo; Tao Ma; Weimin Gao; Yungang Li (Journal of Materials Research and Technology)
The effects of Nb alloying on the organization of Fe–28Mn–10Al–C low-density steels and the form of Nb present in the steels were investigated. Thermodynamics simulation with Thermo-Calc, transmission electron microscopy (TEM), electron backscattering diffraction (EBSD) X-ray diffraction (XRD), metallurgical microscopy, and scanning electron microscopy (SEM) were used to study the presence of Nb and its precipitation characteristics in Fe–28Mn–10Al–C−xNb steels after solid solution treatment at 950 °C. The solubility of Nb in low-density steel and the composition of Nb-containing analytes were also calculated and analyzed. The results revealed that Nb alloying significantly refines the austenite grain structure of Fe–28Mn–10Al–C steel, and based on the basis of microscopic characterization techniques, Nb exists in the form of NbC analytes with a face-centered cubic (FCC) structure in Fe–28Mn–10Al–C−0.5Nb steel and is distributed in a finely dispersed state within the austenite grains and at the grain boundaries. Compared with the test steel without Nb, the Fe–28Mn–10Al–C−0.5Nb low-density steel exhibits superior strength and ductility. Through experimental observations and solid solution theory calculations, the solubility of Nb in the austenite of the Fe–28Mn–10Al–C−0.5Nb steel is less than 0.01 % with the designed alloying composition, the molar fraction of the NbC phase in the Nb-containing precipitates is more than 99.9999 %, and the concentration of Nb in the solid solution and the extent of NbN or Nb(CN) precipitation are very low and negligible. The experimental conclusions obtained from the study and calculations provide a theoretical basis for designing the composition and applying Nb-containing high-manganese and high-aluminum Fe–Mn–Al–C low-density steels.